Soil properties evaluation in horticultural farms of Florencio Varela, Buenos Aires, Argentina - Paladino, Ileana Ruth; Sokolowski, Ana Clara; Irigoin, Julieta; Rodríguez, Hernán A.; Gagey, María Cristina; Barrios, Mónica Beatriz; De Grazia, Javier; Debelis, Silvina; Wolski José Enrique; Buján, Alfonso (Springer, 2018)
The south of the green belt of Buenos Aires is one of the most important producers of fresh vegetables in the province. Only few of the horticultural farmers receive professional agronomic advice. For this reason, an excess of supplies are being used, irrigation water quality is unknown and soils are not analyzed. The aim of this work was to evaluate chemical and physico-chemical characteristics of soils from Florencio Varela, Buenos Aires Argentina, which have not been cultivated for over 20 years (NC), under open-Fields Cultivation systems (FC) and under Greenhouses Cultivation systems (GC). The variables analyzed were: pH in water (pH), Electrical Conductivity (EC), Total Nitrogen (TN), Extractable Phosphorus (EP), Total Oxidizable Carbon (TOC), Oxidizable Carbon associated to Mineral fraction (MOC) and Particulate Oxidizable Carbon (POC). The results showed excess of EP, high pH and loss of oxidizable carbon for FC and GC with respect to NC. Furthermore, an incipient salinity was found in GC. Under FC, EC and TN were lower than GC, probably associated with leaching due to rain. Overfertilization is common in horticultural farming in the green belt, where the worst-case scenario is represented by phosphorus due to its low mobility and high residuality. The problems detected show the need for chemical analysis on soils and irrigation water. This will avoid imbalances due to overfertilization and the use of unsuitable water, thereby preventing soil degradation and aquifer contamination.